Factors Associated With Human IgG Antibody Response to Anopheles albimanus Salivary Gland Extract, Artibonite Department, Haiti, 2017 . (17th June 2022) - Jaramillo-Underwood, Alicia; Impoinvil, Daniel; Sutcliff, Alice; Hamre, Karen E S; Joseph, Vena; Hoogen, Lotus van den; Lemoine, Jean Frantz; Ashton, Ruth A; Chang, Michelle A; Existe, Alexandre; Boncy, Jacques; Drakeley, Chris; et al.
Abstract: Serological data can provide estimates of human exposure to both malaria vector and parasite based on antibody responses. A multiplex bead-based assay was developed to simultaneously detect IgG to Anopheles albimanus salivary gland extract (SGE) and 23 Plasmodium falciparum antigens among 4185 participants enrolled in Artibonite department, Haiti in 2017. Logistic regression adjusted for participant- and site-level covariates and found children under 5 years and 6–15 years old had 3.7- and 5.4-fold increase in odds, respectively, of high anti-SGE IgG compared to participants >15 years. Seropositivity to P. falciparum CSP, Rh2_2030, and SEA-1 antigens was significantly associated with high IgG response against SGE, and participant enrolment at elevations under 200 m was associated with higher anti-SGE IgG levels. The ability to approximate population exposure to malaria vectors through SGE serology data is very dependent by age categories, and SGE antigens can be easily integrated into a multiplex serological assay. Abstract : Malaria infection and transmission involves biting by anopheline mosquitoes. Exposure to these mosquitoes is difficult to measure in humans, but IgG serological data to anopheline salivary proteins were shown to predict vector exposure in Haitian persons.